The Origins and Early Years of a Multicultural Reef Labour Society (Historia, 2021)
The discovery of gold and the proclamation of the main reef in 1886 launched the South African Republic into an economic revolution and so doing created the infrastructure for a complex multicultural Reef labour society. White, Black and Yellow in the diverging positions of capitalist, statesman and labourer converged on the mines - as the largest homogenous section of the Witwatersrand - in an elementary struggle as each strove to give form and stature to his particular position. Foreign ideologies and organizations challenged the locally settled labour man as he grappled with the other cultures and reacted to the forces of developing capitalist exploitation and transitional government legislation.
Keywords: Gold; Goud; Mynwerke; Mining; Main reef; 1886; South African economic revolution; Suid-Afrikaanse ekonomiese revolusie; Witwatersrand; South African Republic; Zuid-Afrikaansche Republiek; Mining industry; Mynindustrie; Black miner; Chinese; Western Europeans